Hyperhidrosis Quality of Life Index (HidroQoL©): further validation and clinical application in patients with axillary hyperhidrosis using data from a phase III randomized controlled trial. (1st September 2020) - Gabes, M.; Jourdan, C.; Schramm, K.; Masur, C.; Abels, C.; Kamudoni, P.; Salek, S.; Apfelbacher, C.
Summary: Background: The Hyperhidrosis Quality of Life Index (HidroQoL©) is a validated patient‐reported outcome measure capturing the quality of life of people affected by hyperhidrosis. Objectives: We aimed to extend the validity evidence to physician‐confirmed diagnosis of primary axillary hyperhidrosis. Methods: Data from a phase III randomized placebo‐controlled clinical trial were used ( n = 171). Confirmatory factor analysis was carried out to confirm the a priori two‐factor structure of the HidroQoL. Internal consistency was assessed using Cronbach's α. Intraclass correlation coefficients (ICCs) were calculated to evaluate test–retest reliability after days –7 to –4. Convergent validity was assessed using correlations with the Dermatology Life Quality Index (DLQI), the Hyperhidrosis Disease Severity Scale (HDSS) and gravimetric sweat production. Known groups were analysed to evaluate discriminative validity. Responsiveness after 29 days was assessed and minimal important difference (MID) values were calculated using both anchor‐ and distribution‐based approaches. All analyses were carried out for total HidroQoL and its two domains. Results: The two‐factor structure of the HidroQoL was confirmed. Internal consistency and test–retest reliability were strong (Cronbach's α 0·81–0·90; ICCs 0·89–0·93). Correlations with other outcome measures were in line with a priori hypotheses. The HidroQoL discriminated between different severity groups ( P ≤ 0·001) and showed sensitivity to change towards improvement ( P < 0·001). An MID value of 4 is proposed for the total scale. Conclusions: This study supports excellent measurement properties including clinical applicability of the HidroQoL in primary axillary hyperhidrosis and suggests a MID of 4 be applied to clinical trial data. Abstract : What is already known about this topic? Hyperhidrosis is characterized by excessive sweating that results in substantial daily life and psychosocial impairments for patients. The Hyperhidrosis Quality of Life Index (HidroQoL©) is a validated instrument for assessing hyperhidrosis‐specific quality of life of people affected by the condition. The HidroQoL was developed and tested in a nonclinic population. What does this study add? This study provides further evidence on the strong measurement properties of the HidroQoL based on a phase III trial in a population of patients with hyperhidrosis. It establishes optimal psychometric performance of the HidroQoL in patients with physician‐confirmed primary axillary hyperhidrosis. It confirms the HidroQoL's ability to detect change based on an interventional study. It establishes a minimal important difference value of the HidroQoL, estimated at a value of 4. What are the clinical implications of the work? The HidroQoL can be used to evaluate the effects of new treatments for axillary hyperhidrosis in clinical trials from the patients' perspective. The HidroQoL is ready to be used in clinical trials in primary axillary hyperhidrosis. Plain language summary available online